WATERFALL METHODS FOR APPLICATION OF ACCOUNTING INFORMATION SYSTEMS IN HOTEL INCOME MANAGEMENT CASE STUDY: CITRA GRAND HOTEL KARAWANG - dede firmansyah saefudin; Widya Apriliah; lham Kurniawan; Yuli Komalasari; Muhammad Faittullah Akbar; Royadi - (Universitas Islam Kuantan Singingi, 2021)
The need for information systems in the business more increase as the same as technological developments in the digital era which give the impacts rapidly changes in all sectors. The accounting cycle in the company is inseparable from the existence of financial recording activities in a certain period. Thus it requires an application to provides the processing financial data or it’s called accounting information system. The Grand Hotel Karawang is the focus of research on building income management accounting information system. Based on the data collection method used: observation, interviews and literature studies (library research), it can be concluded that in managing hotel rental income is still manual or not computerized so that why the research to provide solutions based on the need by designing income accounting information system using waterfall software development method, with phases including needs analysis, design, implementation of program code based on open source in the implementation of the Java programming language to make easier to implement into desktop-based applications. Testing is carried out using blackbox testing as a tool for testing each process step by step in the application that all processes are running well (valid) and can be implemented as needed.